Characteristics and prognosis in heart failure with preserved ejection fraction patients without left ventricular hypertrophy. (14th October 2021) - Nakagawa, Y; Tamaki, S; Yano, M; Hayashi, T; Yamada, T; Yasumura, Y; Hikoso, S; Sotomi, Y; Sakata, Y
Abstract: Background: Clinical heterogeneity exists in heart failure with preserved ejection fraction (HFpEF). Left ventricular (LV) structure in HFPEF is characterized by normal LV cavity size and LV hypertrophy (LVH). However some of HFPEF patients do not have LV hypertrophy, and these patients may have distinct characteristics, Purpose: The purpose of this study is to clarify the clinical characteristics and the prognosis for HFPEF patients without LVH. Methods: We studied 1097 patients, who were hospitalized for acute decompensated heart failure with LVEF ≥50%, and enrolled in the PURSUIT-HFpEF registry. Laboratory testing and echocardiography were examined in the compensated stage (in stable condition after treatment of acute decompensated HF). We divided these patients into 2 groups based on LV mass index (LVMI) in the compensated stage according to the American Society of Echocardiography/European Association of Cardiovascular Imaging recommendations; patients with LVH (48%) and those without LVH (52%). Results: Patients without LVH had significantly lower levels of C-reactive protein and N-terminal pro brain natriuretic peptide (NT-proBNP) and higher levels of estimated glomerular filtration rate in the compensated stage than those with it (p<0.05 for all). Cox hazard regression analysis showed that absence of LVH was favorably associated with the primary composite endpoint of all-cause death, HF rehospitalization, and cerebrovascular events (hazard ratio 0.776, 95% confidence interval 0.620-to 0.970, p<0.05). On the other hand, the frequency of atrial fibrillation (Af) in the decompensated stage was higher in patients without LVH than those with it (52.1% vs 39.3%, p<0.001). Multivariate logistic analysis showed that absence of LVH was independently associated with presence of Af in the decompensated stage (odds ratio=1.520, 95% confidence interval 1.130 to 2.050, P<0.01) Conclusions: HFPEF patients without LVH have less organ damage and favorable prognosis. Af may play a role in the decompensation of HF in HFPEF patients without LVH. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Roche Diagnostics K.K. (Grant number: not applicable)Fuji Film Toyama Chemical Co., Ltd. (Grant number: not applicable)